Anatomical basis to safena cayadus surgical resection Part 2. The sapheno-popliteal Junction - Sánchez Beorlegui, Jesús (2001)
The purpose of this article is to show our experience on the dissection of short saphenous vein during surgical interventions due to essential varicose veins. Between January 1990 and January 2001 forty-seven sapheno-popliteal junctions were dissected in 41 patients. Moreover, we reviewed a broad bibliography regarding the anatomy of sapheno-popliteal junction. We explain both our operative findings and how important the preoperative examination and surgical technique are. One relevant point is to outline the influence of echo-Doppler (ultrasound scan, 1998) and the implementation of standard operative protocols in the quality of anatomical intraoperative diagnoses since 1996.